Modular FEM framework "ModFem" for generic scientific parallel simulations - Michalik, Kazimierz; Banaś, Krzysztof; Płaszewski, Przemysław; Cybulka, Paweł (Computer Science, 2013)
We present the design and its' implementation for a flexible and robust parallel modular finite element (FEM) framework, called ModFem. The design is based on reusable modules which use narrow and well-defined interfaces to cooperate. At the top of the architecture there are problem dependent modules. Problem dependent modules can be additionally grouped together by "super-modules". This structure allows for applying the sequential codes to parallel environments and also support solving multi-physics and multi-scale problems.